PREVALENCE OF THE DIFFERENT MICROBIOLOGICAL LABORATORY ERRORS THAT OCCUR IN PROCESSING BLOOD AND PUS SPECIMENS WITH ESBL POSITIVE E. COLI AT MAKERERE UNIVERSITY CLINICAL MICROBIOLOGY LABORATORY. A CROSS-SECTIONAL STUDY. - Juan, Moureen; Lubwama, Margaret; Nyanganda, Emma Kevin; Nyakake, Ayeebale Rabeeha; Acen, Juliet; Modi, Derick (SJ Insights, 2025)
Background Errors that occur in the diagnostic cycle of the microbiology laboratory cause a delay in the timely and accurate reporting of extended-spectrum beta-lactamase-positiveE. Coli isolated from bloodstream and wound infections. Therefore, this study aimed to determine the Prevalence of The Different Microbiological Laboratory Errors That Occur in Processing Blood and Pus Specimens with ESBL-positive E. Coli. Methodology This study was a cross-sectional retrospective analysis of lab records for ESBL-positive E. coli isolated from blood and pus samples received between the periods of January 2019 to March 2021, A purposive sampling technique was used to select only records for which ESBL-positive E.coli. Results For Bloodstream infections: Out of these 91 request forms; the majority 61(67.03%) had no errors while 30 (32.97%) had errors. These included a missing date, time of reception, and initials of the recipient (60%), sex, age, and patient location (3.33%) missing patient contacts (10%), patient history, and source from which the sample was collected (6.67%). In 16.67% of the request forms physician’s details were not indicated and in 13.33% antibiotics previously used were not indicated. For wound infections; Out of these 85 request forms; the majority 61 (71.76%) had no errors while the minority 24(28.24%) had errors. Some of the errors included missing date, time of reception of samples (33.33%), initials of recipient (33.33%), long collection date (4.167%), patient age (8.33%), patient location, no patient contacts (4.167%), no physician’s details (8.333%) and no antibiotics previously used were not indicated (37.50%). Conclusion More errors were noted in the lab request forms for bloodstream infections (32.97%) as compared to the lab request forms for wound infections (28.24%). Recommendation The lab should work hand in hand with the ward to ensure lab request forms are properly filled out to curb the increasing errors in the lab diagnostic cycle.